Radiolabeling Technique of Silver Nanoparticles (AgNPs) with Iodine-131 Radionuclide - U.N. Sholikhah; R.R. Syahdi; S.E. Permatasari; E. Sarmini; S Sriyono; T. Widyaningrum (Atom Indonesia, 2020)
Radiotherapy is an effective cancer therapy, where a certain dose of radiation is aimed specifically at target and is unaffecting to normal tissue. A selectiveradionuclide must be attached to the specific targeted organ. In this research, silver nanoparticles (AgNPs) were labeled with radionuclide of iodine-131 (131I) to be used in radiotherapy. Silver nanoparticles were synthesized using silver nitrate 0.0005 M, sodium borohydride 0.002 M, polyvinylpyrrolidone 0.3 % (w/v) and natrium chloride 1.5 M, and then followed by purification by centrifugation. Characterization was carried out with UV-Vis spectrophotometer, transmission electron microscope, particle size analyzer, and zeta-sizer. The results show that the maximum absorbance is on a wavelength of 398 nm, spherical shape with a diameter of 10 nm, polydispersity index of 0.455, and zeta potential value of –8 mV. The radiolabeling was done by adding sodium iodide-131 which had been oxidized by chloramine-T and immobilized in AgNPs colloidal solution, and the activity was then measured using a dose calibrator. The identification of radionuclide showed that the sample was free of impurities. The optimum system of radiochemical purity was obtained using Whatman 1 paper strip as the stationary phase and a mixture of methanol: water: ammonium acetate (1:1:1) as the mobile phase, which gave 96 % purity. This method is suitable for radiolabeling AgNPs with 131I to be used for radiotherapy.